Technology for whom? Solar irrigation pumps, women, and smallholders in Nepal - Shrestha, Gitta; Uprety, Labisha; Khadka, Manohara; Mukherji, Aditi (Frontiers Media, 2023)
Agricultural technologies are often promoted as a medium for women’s economic empowerment, which can transform unequal gender relations in rural agrarian societies. This paper investigates three solar irrigation pump (SIP) schemes implemented by state and non-state actors and examines their impacts on women and marginal farmers. We utilize a theory of change framework intended to evaluate the effectiveness of livelihood interventions and guide the design of gender transformative interventions. Our analysis relies on 63 qualitative interviews, 9 key informant interviews and 4 telephonic interviews with social mobilisers from the Saptari District in Nepal. The findings shed light on the unequal social and gender relations that have skewed the adoption and benefits of SIP technology. Gender and social inequalities persist, with limited adoption and benefit of SIP among women and smallholders. Women’s involvement in strategic decisions related to SIP adoptions, installations and usages is limited. This study underscores the importance of strategic interventions that foster meaningful women’s empowerment and ensure equitable distribution and benefits from SIP technology. Assessing the effectiveness of SIPs in empowering women, it is crucial to consider whether the resulting access, ownership, or decision-making opportunities challenge, reinforce, or reproduce unequal gender and social relations.